2011
DOI: 10.1136/bmjopen-2011-000262
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding midwifery unit versus obstetric unit: a matched cohort study of outcomes in low-risk women

Abstract: ObjectiveTo compare perinatal and maternal morbidity and birth interventions in low-risk women giving birth in two freestanding midwifery units (FMUs) and two obstetric units (OUs).DesignA cohort study with a matched control group.SettingThe region of North Jutland, Denmark.Participants839 low-risk women intending FMU birth and a matched control group of 839 low-risk women intending OU birth were included at the start of care in labour. OU women were individually chosen to match selected obstetric/socio-econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(179 citation statements)
references
References 44 publications
12
158
1
8
Order By: Relevance
“…A prospective cohort study from Denmark compared results of two FBCs and two hospital obstetric units. The intrapartum transfer rate from the birth centres was 11.5%, but primiparous women were transferred in greater numbers (36.7%) compared to multiparous women (7.2%) (Overgaard et al, 2011). An American study which included 84 BCs reported an intrapartum transfer rate four times higher among nulliparous compared with multiparous women (Rooks et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A prospective cohort study from Denmark compared results of two FBCs and two hospital obstetric units. The intrapartum transfer rate from the birth centres was 11.5%, but primiparous women were transferred in greater numbers (36.7%) compared to multiparous women (7.2%) (Overgaard et al, 2011). An American study which included 84 BCs reported an intrapartum transfer rate four times higher among nulliparous compared with multiparous women (Rooks et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Evidence from systematic reviews and recently published cohort studies demonstrates that women who give birth in a non-obstetric setting are more likely to have spontaneous vaginal birth and lower rates of intervention, including instrumental birth, episiotomy, oxytocin augmentation and epidural analgesia (Walsh and Downe, 2004;Hodnett et al, 2010; Contents lists available at SciVerse ScienceDirect Overgaard et al, 2011;Birthplace in England Collaborative Group, 2011;Cheung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer rates vary by type of unit ("freestanding" or "alongside") and parity (NICE 2007), but in most if not all such cases the woman will have received the antenatal care package originating in the FMU. While reviews of FMUs focus largely on intrapartum care (Newburn and Singh 2003;Overgaard et al 2011), it is the antenatal care package with which we are interested here because our principal focus is on the risk of preterm birth. We emphasise that this study was concerned with the locus of antenatal care, not with planned or actual place of birth.…”
Section: 'Freestanding' Midwifery Units (Fmu)mentioning
confidence: 99%
“…On the other hand, there is a widely held perception that in the interest of safety, as many women as possible should birth in higher-level maternity units such as tertiary maternity units (TMUs) where specialist obstetric, anaesthetic and neonatal intervention is available on site (NSW Health Department, 2002b; The Royal Australian and New Zealand College of Obstetricians and Gynaecologists, 2005). One of the major concerns about FMUs is the potential delay in treatment in the event of transfer to tertiary care via car or ambulance, which could lead to serious adverse outcomes (Overgaard et al, 2011). The question is: Are there significant differences in outcomes of labour and birth for women who plan to give birth at FMUs compared to women of similar risk status who plan to give birth at TMUs?…”
Section: Introductionmentioning
confidence: 99%